In Vitro Evaluation of Fungicides against Fusarium solani, the Causative Agent of Brinjal Root Rot - Ghimire, Rukmita; Shrestha, Ram Kumar; Shrestha, Jiban (Indonesian Journal of Agricultural Research, 2021)
Root rot in brinjal is one of the most important problems. In the present research, five different fungicides; Mancozeb, Copper oxychloride, Hexaconazole, Metalaxyl+Mancozeb, and Carbendazim, at 100 ppm were evaluated for their efficacy against the causative agent of this disease, Fusarium solani, In-vitro. The experiment was carried out in Completely Randomized Design with seven replications. Our result shows the difference in the efficacy of all tested fungicide against this pathogen. The application of Carbendazim at 100 ppm gave the highest inhibition of mycelium growth (100%) followed by Mancozeb (85.08%) and Metalaxyl+Mancozeb (64.3%) (at the same dose) on the 7th day of incubation suggesting Carbendazim (100 ppm) as a better one to use for the management of F. solani.